The Role of Biodiversity Potential in Sustainable Ecotourism Development Strategy: A Case Study of Mount Sigogor Nature Reserve and Mount Picis Nature Reserve - Kurniawan, Nur Patria; Komara, Liris Lis (SAFE-Network, 2025)
The Mount Picis and Mount Sigogor Nature Reserves in Ponorogo Regency, East Java, are conservation areas with significant potential for high biodiversity, including habitats for protected species such as the Javan Hawk-eagle and the Javan Leopard, as well as vital environmental services. This study aims to formulate a strategy for developing sustainable ecotourism-based nature tourism in the Mount Picis and Mount Sigogor Nature Reserves, Ponorogo Regency. The data from this study were analyzed using the SWOT method, identifying internal and external factors. The area's main strengths include its ecosystem integrity and rich flora and fauna diversity, while opportunities came from local government support and the participation of buffer communities. However, significant weaknesses include limited management facilities and infrastructure, suboptimal area data, and external threats such as low community well-being and the risk of forest fires. Based on this analysis, two main strategic objectives were formulated: (1) Increasing research and education based on biological potential, and (2) Maintaining the security and integrity of the area. The implementation strategy includes developing a potential database, adding infrastructure, improving human resources, and securing the area integrated with the economic empowerment of communities in the buffer zone. The conclusion of this study is that ecotourism development in the Picis mount and Gunung mount Nature Reserve must be carried out adaptively, prioritizing conservation, and involving the active participation of local communities to ensure the sustainability of the ecological and social functions of the area.